THE EFFECT OF ORGANIC FERTILIZING KIRINYUH (Chromolaena odorata L.) AND PHONSKA FERTILIZER AGAINST CHEMICAL PROPERTIES OF PLANTED TAILINGS SOIL RICE FIELD - Willens Christano Anyo; Tommy D. Sondakh; Jenny J. Rondonuwu; Tommy B. Ogie (Sam Ratulangi University, 2021)
This study aims to determine the effect of kirinyuh organic fertilizer and phonska fertilizer on changes in the properties of tailings soil and the growth and production of upland rice. Land tailings are taken from the location of the wilayah pertambangan rakyat (WPR) in Tatelu Village, Dimembe District, North Minahasa Regency. And the research was carried out at the Green House, Faculty of Agriculture, Sam Ratulangi University. This study was designed using a completely randomized design (CRD) with a factorial pattern consisting of two factors, namely: Factor I is kirinyuh organic fertilizer (A) which consists of 4 (four) levels: A0 = 0g / polybag, A1 = 300g / polybag, A2 = 600g / polybag, A3 = 900g / polybag and Factor II which is Phonska Fertilizer (B) consisting of three levels: B0 = 0g / polybag, B1 = 1,5g / polybag, and B2 = 3g / polybag. Each poly bag is filled with soil up to 20 kg.Keywords: Kirinyuh; Phonska; Land of Tailings.AbstrakPenelitian ini bertujuan untuk melihat pengaruh pemberian pupuk organik kirinyuh dan pupuk phonska terhadap perubahan sifat kimia tanah tailing dan pertumbuhan serta produksi padi ladang. Pengambilan Tanah Tailing diambil dari lokasi Wilayah Pertambangan Rakyat (WPR) di Desa Tatelu, Kecamatan Dimembe, Kabupaten Minahasa Utara. Dan Penelitian dilaksanakan di Rumah Kaca Fakultas Pertanian Universitas Sam Ratulangi. Penelitian ini dirancang dengan menggunakan Rancangan Acak Lengkap (RAL) dengan pola faktorial yang terdiri dari dua faktor yaitu : Faktor I yakni pupuk organik kirinyuh (A) yang terdiri dari 4 (empat) taraf : A0 = 0g / polybag, A1 = 300g / polybag, A2 = 600g / polybag, A3 = 900g / polybag dan Faktor II yakni Pupuk Phonska (B) yang terdiri dari tiga taraf : B0 = 0g / polybag, B1 = 1,5g / polybag, dan B2 = 3g / polybag. Setiap polybag diisi tanah sampai seberat 20 kg.Kata Kunci: Kirinyuh; Phonska; Tanah Tailing.